Feminist Forum at the SCSC: Teaching and Activism in a Transformed Landscape - Brammall, Kathryn M. (The sixteenth century journal, 2017)
An introduction is provided to articles within the issue, which is part of the forum titled "Feminism in the New Millennium," with topics, including teaching women's history from a feminist perspective, the construct of the artist-genius and author Sor Juana Ines' feminist activism.